A Model for Study Table Designed for Freshmen Athletes - Lee, Naomi P.; Harney, Mark K. (My University, 1985)
A study table program was designed and evaluated, including having a student proctor class checking freshmen athletes and meeting with them to review class material. Students who met a benchmark at mid-semester had reduced study table hours as an incentive. The program showed an increase in student GPA above the previous year's freshmen athletes and non-athletes as well.
Keywords: study hall; academic support; freshmen